Spiritual Needs of Pregnant Women - Wahyuni, Sri; Istikhomah, Henik; Murwati, Murwati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
The pregnancy period is a condition that makes the mother's life more meaningful and the use of spirituality as a strong coping mechanism, thus it is necessary to provide services to increase the mother's spirituality starting from the pregnancy period. The aim of this research is to identify the spiritual needs of pregnant women. This research is qualitative using descriptive method. Data collection with focus group discussions with clergy from five religions (Islam, Christianity, Catholicism, Hinduism and Buddhism) and the midwives based on the Patients Spiritual Needs Assessment Scale. Data was analyzed using conventional content analysis. Spiritual needs based on spiritual informants were identified as follows: patience, meaning that pregnant women are able to endure things they don't like, discomfort during pregnancy and continue to try with a pleased and pleased heart and surrender to God. Gratitude means that as a pregnant mother she expresses gratitude to God, does not complain and expresses feelings of relief, joy and praise to God and doing good for what she has. The pleased is interpreted as meaning that pregnant women can accept everything that happens happily and realize that everything that happens is God's will. The ability to learn lessons means that pregnant women can use the condition of pregnancy as a lesson and take advantage of it and then use it as a basis for moving on in life. The results of consultation with language experts found that the answer options used a Likert scale, the content was related to the concept of pregnancy and spiritual concepts, several items were made unfavorable as a control function. The results of identifying spiritual needs are used as the basis for proposals to improve holistic midwifery care.